THE EFFECT OF APPLICATION A MODIFIED T-MODEL PLATE ON GD2JPP LEVELS AND AVERAGE GLYCEMIC LOAD OF DMT2 PATIENTS MENU - Mabas, N. Sahila Sukma W. P.; Dwipajati, Dwipajati; Widajati, Endang (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Background: Type 2 Diabetes Mellitus (DM) is a metabolic disease with a high prevalence in Indonesia. Its management emphasizes TNM using the